India-Pakistan Security Dilemma: Analyzing the Deterrence and Coercive Diplomacy in the Context of Regional Stability - Raeesa, Umme; Akhtar, Nasreen (Journal of Development and Social Sciences, 2025)
The main objective of this paper is to analyze the alteration of military doctrines by India and Pakistan with tactical nuclear weapons establishes a fragile balance of power where an attempt to live peacefully becomes threatening. This article also assesses the effect of external alignments on the escalation dynamics between both countries, such as a growing alignment between India and America, on one hand and Pakistan establishing a strategic link with China. Using a qualitative, comparative case study method from ‘Security Dilemma Theory’ within the realist paradigm, the research reveals the relatively under-studied yet useful tool of coercive diplomacy in India-Pakistan relations. Through an examination of this two-track approach, this article offers informative recommendations for scholars and policymakers that seek to curb threats and secure sustainable peace for South Asia. We have employed interpretative methodology in understanding the existing security environment between India and Pakistan.